Iris pigment epithelial cysts in acute lymphoblastic leukemia-a case report - Kar Yong, Chong; Yong Zheng, Wai; Nurhayati, Abdul Kadir; Lik Thai, Lim; Raja Muhamad Zul, Hatta; Wai Seng, Chiang (BioMed Central Ltd, 2025)
Background Iris cysts are classified as either primary or secondary, with further subcategorization based on the tissue of origin. The most common type is the primary iris pigment epithelial (IPE) cyst. We report a rare case of bilateral IPE cysts in a patient with acute lymphoblastic leukemia (ALL). Case presentation A 3-year-old male toddler initially presented with signs and symptoms of anemia. Multiple lymph nodes were palpable throughout the body, and hepatosplenomegaly was noted. An incidental finding of cystic lesions at the margins of both pupils prompted referral to the ophthalmology team. There was no family history of malignancy or similar eye conditions. Ophthalmic examination revealed IPE cysts in both eyes (BE). Fundus examination showed a dull macula, and tortuous vessels, with no retinal hemorrhages observed. Intraocular pressure was normal. Petechial rashes were present on both eyelids. A full blood count revealed pancytopenia, and a peripheral blood film (PBF) showed a leucoerythroblastic picture without obvious blast cells. Bone marrow aspiration and trephine biopsy (BMAT) were performed. Trephine biopsy and bone marrow immunophenotyping were suggestive of B-cell acute lymphoblastic leukemia (B-cell ALL) with aberrant CD58 expression. Cytogenetic analysis revealed hyperdiploidy, a favourable prognostic marker. The patient was started on chemotherapy. Following initiation of chemotherapy, the IPE cysts decreased in size. Conclusion In this case, the IPE cysts were likely associated with ALL. This rare occurrence may raise awareness of a potential link between IPE cysts and hematological malignancies, and could pave the way for future research to elucidate the underlying pathogenesis and treatment implications.